Centering gender in sustainable palm oil of Indonesia: A systematic literature review - Ngoyo, Muh Fardan; Andriani, Shadry; Darwin, Dirmansyah; Nugraha, Putu Ananda Devi; Zulkarnaen, Adi (Privietlab, 2026)
As a major agricultural commodity in Indonesia, palm oil plays a significant role in economic development, especially in rural livelihood and poverty reduction. However, the current dynamics of palm oil expansion have attracted global attention toward social responsibility and environmental degradation, including gendered impacts that remain underexplored in sustainability narratives. This systematic review examines the incorporation of gender analysis in studies on sustainable palm oil in Indonesia, focusing on conceptual frameworks, methodological approaches, and policy implications. Bibliometric data were retrieved through Publish or Perish (PoP), collecting relevant literature from Scopus and Google Scholar from 2010-2025, complemented by keyword search strings in English and Bahasa Indonesia. For clustering and data visualization, this study employed VoSviewer to visualize and analyze keyword associations, trends, and thematic clusters. Preliminary findings indicate that while the sustainability literature on palm oil is extensive, gender-related studies are limited and often fragmented, with conceptualizations of gender varying from labor to land rights and participation. This study finds a cluster of publications focusing on the solid grounding of a feminist lens, while others pay more attention to gender roles, lived experience, and policy and practices at the regulation level. This review highlights critical gaps in integrating gender perspectives into sustainability initiatives and calls for more nuanced, intersectional approaches to ensure equitable outcomes in the palm oil sector. By synthesizing existing evidence, this study provides insights into strengthening gender-responsive sustainability strategies in Indonesia’s palm oil sector.